Por um Teatro do Devir: a criação em processo no diálogo da Trupe Motim com o Teatro de Tadeusz Kantor - Fonseca, José Flávio Gonçalves da (2016)
The following dissertation presents itself as a record of a trace of passage in a trial that takes place within the processuality in the scenic creation. The research proposed here of the dialogue drawn between the theatre of the polish artist Tadeusz Kantor and the collective of artists of the city of Quixeré, Ceará, called Trupe Motim. To this end this dialogue was effective from the perception regarding the procedural character present in the poetry of Tadeusz Kantor who served as a trigger for carrying out creative work by the Trupe Motim. In the course of the research process, problematized is the act of rehearsing, bringing as discussion this as a research method, straining the relationship of research in art, that is, the process itself as a research method in contrast to the methods of classical research. Thus, the path traced in this work is to question the art of relationship in their self-referential aspect, bringing to the discussion, the dynamics of molecular and molecular flows from the framework of the philosophy of Deleuze & Gattari. Thus, the made experiment takes place in the context of the match between the molar flow and molecular as it questions the idea of art work finished and seeks to work on the idea of a work that takes place in its procedural aspect and in that sense, opens to the scenic realization as a building becoming. These above aspects are even show the actual presentation of this dissertation playing with breaking the regulation, since proposes a reading that takes place amid the possibilities of chance, giving thus also in a reading process.